Endogenous Depopulation And Economic Growth - Alberto Bucci; Klaus Prettner (Global Labor Organization (GLO), 2025)
Fertility rates have declined dramatically across almost all highincome countries over the past decades. This has raised concerns about future economic prospects. Indeed, fully- and semi-endogenous growth models imply that a shrinking workforce would lead to declining income growth and perhaps even stagnation. We extend the previous analyses to explicitly incorporate an endogenous quantity/quality trade-off between fertility and human capital accumulation. This allows us to assess the extent to which a declining number of workers can be compensated by increasing education. Our analysis demonstrates that economic growth needs not necessarily to decline with a falling population. Under certain conditions, human capital investment can sustain technological progress and economic growth despite the demographic challenges we are facing.
Keywords: J11; J13; O33; O41; I25; 330; Demographic Change; Fertility Decline; Economic Growth; Research and Development; Endogenous Fertility; Endogenous Education; Human Capital Accumulation